Correlated functional connectivity and glucose metabolism in brain white matter revealed by simultaneous MRI/positron emission tomography. Issue 3 (26th November 2021) - Guo, Bin; Zhou, Fugen; Li, Muwei; Gore, John C.; Ding, Zhaohua
Abstract: Purpose: There has been converging evidence of reliable detections of blood oxygenation level dependent (BOLD) signals evoked by neural stimulation and in a resting state in white matter (WM), within which few studies examined the relationship between BOLD functional signals and tissue metabolism. The purpose of the present study was to explore whether such relationship exists using combined functional MRI and positron emission tomography (PET) measurements of glucose uptake. Methods: Functional and metabolic imaging data from 25 right‐handed healthy human adults (aged 18–23 years, 18 females) were analyzed. Measures, including average resting state functional connectivity (FC) with respect to 82 Brodmann areas, fractional amplitude of low‐frequency fluctuations (FALFF), and average fluorodeoxyglucose (FDG) uptake by PET, were computed for 48 predefined WM bundles. Pearson correlations across the bundles and 25 subjects studied were calculated among these measures. Linear mixed effects models were used to estimate the variance explainable by a predictor variable in the absence of inter‐subject variations. Results: Analysis of six separate imaging intervals found that average FC the bundles was significantly correlated with local FDG uptake ( r  = 0.25, p  < 0.001), and the FC also covaried significantly with FALFF ( r  = 0.41, p  < 0.001). When random effects from inter‐subject variations were controlled, these correlations appeared to be medium to strong ( r  = 0.41 for FC vs. FDG uptake, and r  = 0.65 for FALFF vs. FC). Conclusion: This study indicates that BOLD signals in WM are directly related to variations in metabolic demand and engagement with cortical processing and suggests they should be incorporated into more complete models of brain function.